Kadar Mineral Makro dalam Serum Kambing Peranakan Ettawa yang Secara Klinis Sehat (SERUM MACROMINERALS CONCENTRATIONS IN CLINICALLY HEALTHY ETTAWA CROSSBRED GOATS) - Widiyono, Irkham; ., Sarmin (Jurnal Veteriner; Vol 13 No 2 (2012), 2013)
A study to evaluate the serum macrominerals status in clinically healthy Ettawa crossbred goatshave been carried out in order to obtain the baseline data for monitoring health condition. A total of 60Ettawa crossbred goats were used in the study. The demographic characteristics of the animals groupwere: (i) young male and female goats (5-8 months); (ii) adult male and female goats (1.5 – 4 years); (iii)pregnant, and (iv) lactating animals. The serum macrominerals concentrations were within the referencestatus of other small ruminant species. The mean calcium (Ca), potassium (K), and chloride (Cl)concentrations were not significantly difference (P>0.05) between the animals groups. The Na concentrationof adult female goats was 139.33 ± 1.94mmol/L and was significantly lower compared to the animals inthe other groups (P<0.05). The inorganic phosphor (Pi) concentrations in pregnant and lactating animalswere significantly lower (P<0.05) compared to that in young, adult, male and female goats. The macromineralsconcentration in serum was influence by the physiological status of the animals.
Keywords: Ettawa crossbred goats, serum macrominerals